Breaking the silence: Determining Prevalence and Understanding Stillbirth Stigma. (February 2021) - Pollock, Dr Danielle; Pearson, Dr Elissa; Cooper, Dr Megan; Ziaian, Associate Professor Tahereh; Foord, Claire; Warland, Associate Professor Jane
Abstract: Background: The 2011 and 2016 Stillbirth Lancet series made a call to action to identify mechanisms to reduce stillbirth stigma. This research answers that call, investigating the extent and dimensions of stillbirth stigma experienced by an international sample of mothers bereaved by stillbirth. Objective: To determine the prevalence and type as well as explore explanatory variables associated with higher levels of stillbirth stigma with bereaved mothers in high-income countries (Australia, United Kingdom, The United States of America and New Zealand). Method: An international survey of 889 bereaved mothers was conducted utilising the recently developed Stillbirth Stigma Scale to explore the extent and types of stigma experienced, as well as the association between stigma and self-esteem (Rosenberg Self- Esteem Scales), perinatal grief (Perinatal Grief Scale), and perceived social support (Perceived Social Support Scale). Demographic information (e.g. age, education, stillbirth history, sexual orientation and mental health) were collected to determine the association between individual demographic factors and stillbirth stigma. Results: Results of the Stillbirth Stigma Scale indicated that a majority (54%) of bereaved mothers experienced stigma. Self-stigma was the predominant type of stigma experienced (80%), followed by perceived devaluation (64.9%). Bereaved mothers also experienced discrimination (29.1%) and issues with disclosing their stillbirth to their community (36.7%). Stillbirth stigma scores were higher in bereaved mothers who had experienced the loss of their first child. High scores were associated with the mother's mental health status (diagnoses prior to stillbirth, and/or after stillbirth (p<.05)).The other scales used indicated that higher stillbirth stigma scores were also associated with lower self-esteem (r (877) =-.304, p<.001), lower perceived social support (r (871) =-.448, p<.001) and higher levels of grief (r (829) =.609, p<.001). Conclusion: The current research was the first to identify that 54% of bereaved mothers experienced stigma, with self-stigma being the most prominent. Bereaved mothers endured discriminating experiences and had trouble disclosing their stillbirth to others within their community. The first-time mother with a self- reported history of mental illnesses appears to be the most at-risk of higher levels of stigma. Future longitudinal research needs to be conducted to determine the direction of the explanatory variables i.e. mental health, self-esteem and social support and develop interventions, which support the bereaved mother and reduce stillbirth stigma. Relevance: This study is the first to demonstrate the prevalence, extent, type and explanatory variables of stigma reported by bereaved mothers and the association between this and poorer outcomes including increased grief and decreased self-esteem. This study begins a dialogue about prevalence and explanatory variables of stillbirth stigma and its impact, to inform future prevention and support potential stigma reduction programs for community and bereaved mothers.